The syntax of argument structure: empirical advancements and theoretical relevance - Alexiadou, Artemis; Verhoeven, Elisabeth (Linguistische Arbeiten, 2021)
Frontmatter -- Contents -- The syntax of argument structure -- Too strong argument structures and (un-)prepared repair -- Evidence against lexicalist or configurational approaches to structural encoding in sentence production -- Case marking affects the processing of animacy with simple verbs, but not particle verbs -- Unexpected (in)animate argument marking -- Interpretability, aspectual coercion, and event structure in Object-Experiencer verbs: An acceptability study -- Discourse and unaccusativity -- Index
Keywords: Aufsatzsammlung; Empirische Linguistik; Argumentstruktur